Soulless Matter, Seats of Energy. Metals, Gems and Minerals in South Asian Tradition, edited by Fabrizio M. Ferrari and Thomas W. P. Dähnhardt - Smith, Frederick (Religions of South Asia, 2019)
Soulless Matter, Seats of Energy. Metals, Gems and Minerals in South Asian Tradition, edited by Fabrizio M. Ferrari and Thomas W. P. Dähnhardt. Sheffield: Equinox, 2016. xxxii + 282 pp., £22.95/29.95 (pb). ISBN 978-1-78179-129-5.